The Impact of a Resident Communication Skills Curriculum on Patients' Experiences of Care. Issue 3 (1st February 2016) - Mitchell, John D.; Ku, Cindy; Wong, Vanessa; Fisher, Lauren J.; Muret-Wagstaff, Sharon L.; Ott, Qi; Shahul, Sajid; Bose, Ruma; Tibbles, Carrie; Jones, Stephanie B.
Abstract : Despite the high impact of lapses in communication skills on patient care, these skills are often not explicitly taught in residency training programs. We implemented a simulation and web-based curriculum in communication for anesthesia residents and used a patient survey adapted from the Four Habits Coding Scheme to detect changes in patient feedback on residents' communication skills after the curricular intervention. Postintervention mean ratings of residents for the overall survey were higher than preintervention mean ratings. Future research will focus on assessing the curriculum's effectiveness and exploring the generalizability of the survey and curriculum. Abstract : Supplemental Digital Content is available in the text.